Causal Association Between Obstructive Sleep Apnea and Migraine: A Bidirectional Mendelian Randomization Study - Wang YP; Wei HX; Hu YY; Zhang C; Niu YM (Nature and Science of Sleep)
Yu-Pei Wang,1,* Hui-Xia Wei,2,* Yuan-Yuan Hu,3 Chao Zhang,4 Yu-Ming Niu3– 5 1Department of Stomatology, Taihe Hospital, Hubei University of Medicine, Shiyan, Hubei, 442000, People’s Republic of China; 2Department of Anesthesiology, Taihe Hospital, Hubei University of Medicine, Shiyan, 442000, People’s Republic of China; 3Department of Stomatology, Gongli Hospital of Shanghai Pudong New Area, Shanghai, People’s Republic of China; 4Center for Evidence-Based Medicine and Clinical Research, Taihe Hospital, Hubei University of Medicine, Shiyan, Hubei, 442000, People’s Republic of China; 5Hubei Key Laboratory of Embryonic Stem Cell Research, Hubei Provincial Clinical Research Center for Umbilical Cord Blood Hematopoietic Stem Cells, Taihe Hospital, Hubei University of Medicine, Shiyan, Hubei, 442000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yu-Ming Niu, Department of Stomatology, Gongli Hospital of Shanghai Pudong New Area, Shanghai, People’s Republic of China, Tel +86 13581370999, Email niuyuming@yeah.net Chao Zhang, Center for Evidence-Based Medicine and Clinical Research, Taihe Hospital, Hubei University of Medicine, Shiyan, Hubei, 442000, People’s Republic of China, Email zhangchao0803@126.comObjective: Patients with obstructive sleep apnea (OSA) frequently suffer from migraine, however the causal relationship between OSA and migraine is unknown. Investigating the causation will assist in understanding the etiology of OSA and migraine.Methods: Bidirectional two-sample Mendelian randomization (MR) and multivariable MR (MVMR) approaches were carried out to investigate the causal link between OSA and migraine. The public genome-wide association study (GWAS) data for OSA, migraine, and subtypes were obtained from the IUE open GWAS project and the FinnGen consortium. To investigate the causal links between OSA and migraine, inverse variance weighted (IVW) analysis was used in conjunction with four additional statistical approaches. Furthermore, sensitivity studies were performed using heterogeneity and pleiotropy tests to assess the estimation’s robustness.Results: In general, our findings suggested that the OSA is causally associated with migraine with aura (MA, IVW: OR = 1.147; 95% CI = 1.016– 1.295; P = 0.026), which was confirmed with the MVMR analysis further (OR =  1.184, 95% CI = 1.028– 1.364, P =  0.020). In addition, increased risk of migraine and migraine without aura on OSA occurrence were identified in the reverse analysis, but these results were subsequently negated with MVMR analysis.Conclusion: According to the current findings, there was a preliminary causal effect of OSA on MA among European descendants.Clinical Relevance: These findings suggest a potential causal effect of OSA on migraine and provide new insights to prevent and manage the two disorders.Keywords: obstructive sleep apnea, migraine, Mendelian randomization, causal effect